The political motives of party elites and public responses in Twitter: The idea of postponing Indonesia’s 2024 election - Dimas Subekti; Didi Rahmadi; Ridho Al-Hamdi (Masyarakat, Kebudayaan dan Politik, 2023)
The 2024 election has become Indonesia’s political agenda to carry out elite circulation in a timely manner, but the political party elite threw out the idea of postponing these activities. Therefore, this study aims to explain the political motive of party elites and responses on Twitter about the idea of postponing the 2024 Indonesian elections. This study uses a qualitative method with a descriptive approach. This study also uses NVivo 12 Plus software as a data analysis tool. The findings in this study are that the political motives of Muhaimin Iskandar, Zulkifli Hasan and Airlangga Hartarto in raising the idea of postponing the 2024 election tend to be material-intensive motives. Meanwhile, the content and narrative of Twitter netizen responses tend to lead to rejection of the idea of postponing the 2024 election. Twitter netizens prefer the 2024 elections to be held according to a predetermined schedule. The conclusion in this study is that the idea of postponing elections, which is dominated by the private interests of the elite, is not responded positively by the public. This has implications for the emergence of public distrust of private elites and their political parties.